2019
DOI: 10.7287/peerj.preprints.27557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fish nursery value of algae habitats in temperate coastal reefs

Abstract: The nursery function of coastal habitats is one of the most frequently mentioned and recognized ecosystem services in the valuation of coastal ecosystems. Despite its importance our understanding of the precise habitat parameters and mechanisms that make a habitat important as a nursery area is still limited for many species. The study aimed to establish the importance of different algae morphotypes in providing shelter and food for juvenile coastal fish during the main settlement peaks in early spring and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…A lot of the work on temperate macroalgae and nursery provision for coastal fish is from the Mediterranean (see Figure 2 and Table 1). Perennial macroalgae belonging to the genus Cystoseira, which has a tree-like morphology, can form dense meadows over rocky-bottoms in the Mediterranean and are referred to as Cystoseira forests (Hinz et al, 2019). These highly structured habitats potentially provide both shelter from predation and an abundance of food (with Cystoseira forests containing more prey than other less structured algal morphotypes) making them high quality foundation-species nursery areas in addition to seagrasses in the Mediterranean (Hinz et al, 2019).…”
Section: Temperate Macroalgae Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of the work on temperate macroalgae and nursery provision for coastal fish is from the Mediterranean (see Figure 2 and Table 1). Perennial macroalgae belonging to the genus Cystoseira, which has a tree-like morphology, can form dense meadows over rocky-bottoms in the Mediterranean and are referred to as Cystoseira forests (Hinz et al, 2019). These highly structured habitats potentially provide both shelter from predation and an abundance of food (with Cystoseira forests containing more prey than other less structured algal morphotypes) making them high quality foundation-species nursery areas in addition to seagrasses in the Mediterranean (Hinz et al, 2019).…”
Section: Temperate Macroalgae Habitatsmentioning
confidence: 99%
“…Perennial macroalgae belonging to the genus Cystoseira, which has a tree-like morphology, can form dense meadows over rocky-bottoms in the Mediterranean and are referred to as Cystoseira forests (Hinz et al, 2019). These highly structured habitats potentially provide both shelter from predation and an abundance of food (with Cystoseira forests containing more prey than other less structured algal morphotypes) making them high quality foundation-species nursery areas in addition to seagrasses in the Mediterranean (Hinz et al, 2019). Although Cystoseira forests used to dominate Mediterranean rocky reefs, these forests are being replaced by less complex Dictyotales dominated bushland, algal turfs or barren grounds as a result of numerous anthropogenic pressures, such as water pollution, invasive species, overfishing and physical disturbances (Cheminee et al., 2017).…”
Section: Temperate Macroalgae Habitatsmentioning
confidence: 99%
“…Habitat and seascape tri-dimensional structure can be qualified by its heterogeneity and complexity 83,84 . Generally high quality habitats for juvenile fishes are recognized to be associated with high degrees of three-dimensional structuration 85 , in terms of both complexity 46,48,86,87 and/or heterogeneity 36 . Natural rocky habitats (RS) presented a high structural and biological complexity due to different macrophytes assemblages, and indeed supported the highest mean species richness and abundance of juvenile fishes whatever the period.…”
Section: Habitats Used By Juvenile Fish In Mediterranean Shallow Coasmentioning
confidence: 99%
“…However, the higher abundance of juveniles in seagrass bed habitats and rocky substrates during the warm period could be related to the greater protection and food resources provided by the greater canopy height of Posidonia oceanica and macroalgae communities 45,46,48 . The role of highly complex Cystoseira forest canopies with regard to the composition of juvenile fish assemblage was well studied by Cheminée et al 45,46 , Cuadros et al 47 and Hinz et al 48 , who demonstrated that Symphodus spp., Labrus spp. and Serranus spp.…”
Section: Importance Of Both Local Habitat Characteristics and Large-smentioning
confidence: 99%
See 1 more Smart Citation